Makroenkapsulasi Ekstrak Lidah Buaya (Aloe vera): Uji Karakteristik Mikro-Enkapsul dan Aktivitas Anti-Oksidannya = Microencapsulation Extract of Aloe Vera: Test of Characteristic of Encapsule and Its Anti-Oxidant Activi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Study of microencapsulation Aloe vera extract using mixture of Arabic gum-maltodextrin encapsulant and ratio of Aloe vera extract to encapsulant was undertaken. The characteristics of microencapsule consisting of yield, moisture content, water activity (aw), density, solubility in water, total phenolic, anti-oxidant activity were determined, while the appearance of microencapsule was observed using electron microscope. The ratio a mixture Arabic gum to maltodextrin encapsulant and the ratio Aloe vera extract to encapsulant had an obvious effect on yield, moisture content, water activity (aw), density, solubility in water, total phenolic, anti-oxidant activity and also on the appearance of microencapsule. Microencapsulation extract of Aloe vera with ratio of Arabic gum to maltodextrin (2:3) and ratio of Aloe vera extract to encapsulant (1:6) produced the best microencapsule and it was characterized by approximately 41.30% of yield, and 10.25% db of moisture content. The water activity (aw) was 0.20. Density, solubility in water, and total phenolic of microencapsule were 0.44 g/cm3, 93.31%, and 105.70 mg/g, respectively. Anti-oxidant activity was approximately 41.17%.